Pelatihan Instalasi Sistim Listrik Tenaga Surya kepada Santri Dayah Mini Banda Aceh - Mahdi Syukri; Suriadi; Ramdhan Halid Siregar; Syahrizal; Alfisyahrin (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2022)
Utilization of solar energy as a generator of electrical energy is growing. One of technology for the use of solar energy is to use solar panels to generate electricity. Solar panels can be installed on the roof of the house to meet electricity on a household scale. The current challenge is the lack of trained personnel who have the competence to install solar panels on the roof of the house. So it is considered it is important to educate skilled workers through solar power installation training. For this purpose, training activities for solar electricity installation are carried out for Dayah Mini Banda Aceh students through an independent community service program. This training aims to train workers to gain Panel installation competence Sun on the Roof of the House. Solar Panel Installation Practice Method is done by simulating installation of equipment ranging from solar panels, inverters, charge controllers and charging battery. The results to be achieved with the practice of installing solar panels so that students have Skills in installing rooftop solar panels.